1995
DOI: 10.1016/0378-1097(94)00489-e
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression in Saccharomyces cerevisiae of the Lactococcus lactis mleS gene encoding the malolactic enzyme

Abstract: Malolactic fermentation, a crucial step in winemaking, results mostly in degradation by lactic acid bacteria of L-malic acid into L-lactic acid. This direct decarboxylation is catalysed by the malolactic enzyme. Recently we, and others, have cloned the mleS gene of Lactococcus lactis encoding malolactic enzyme. Heterologous expression of mleS in Saccharomyces cerevisiae was tested to perform simultaneously alcoholic and malolactic fermentations by yeast. mleS gene was cloned in a yeast multicopy vector under a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Genetic engineering of wine yeast to conduct alcoholic fermentation and malate degradation simultaneously has been explored by several groups. In order to engineer a malolactic pathway in S. cerevisiae the malolactic genes (mleS) from Lactococcus lactis, [2,3,11,28] Lactobacillus delbrueckii [184] and the mleA gene from O. oeni [83] were cloned and expressed in S. cerevisiae. The mleS gene encodes a NAD-dependent malolactic enzyme that converts L-malate to L-lactate and carbon dioxide [28].…”
Section: Bio-adjustment Of Wine Aciditymentioning
confidence: 99%
“…Genetic engineering of wine yeast to conduct alcoholic fermentation and malate degradation simultaneously has been explored by several groups. In order to engineer a malolactic pathway in S. cerevisiae the malolactic genes (mleS) from Lactococcus lactis, [2,3,11,28] Lactobacillus delbrueckii [184] and the mleA gene from O. oeni [83] were cloned and expressed in S. cerevisiae. The mleS gene encodes a NAD-dependent malolactic enzyme that converts L-malate to L-lactate and carbon dioxide [28].…”
Section: Bio-adjustment Of Wine Aciditymentioning
confidence: 99%
“…No color change was observed with CBT313 carrying pJF119HE. L-Malate uptake was checked by using L-[ 14 VOL. 62,1996 MALOLACTIC GENES FROM LEUCONOSTOC OENOS 1279 lation was observed in the strain carrying pJF119HE (Fig.…”
Section: Cloning Of the Mle Locus From Leuconostoc Oenosmentioning
confidence: 99%
“…A positive regulatory gene called mleR, which is responsible for activation of the malolactic system was described first (38). Recently, cloning, sequencing, and heterologous expression of the MLE gene from Lactococcus lactis (1,13,14) have been described. A sequence alignment of the protein revealed that there are three highly conserved regions that are also present in proteins that belong to the malic enzyme family.…”
mentioning
confidence: 99%
“…Strains of Saccharomyces cerevisiae can only metabolize malate to a limited extent (see Radler, 1993 for a review) and strains of Leuconostoc oenos are currently used to deacidify wine. Several attempts have been made to introduce the bacterial malolactic gene into S. cerevisiae (Ansanay et al, 1993;Denayrolles et al, 1995;Williams et al, 1984). However, the recombinant yeast strains were unable to degrade malate effectively to L-lactate.…”
Section: Introductionmentioning
confidence: 99%